ANALISIS PENGENDALIAN INTERN TERHADAP SISTEM PENJUALAN PADA PT. TRAKINDO UTAMA CABANG TERNATE - Karim Abubakar (Jurnal Manajemen Sinergi, 2016)
This research explain how the internal control of the system sales conducted by the company is already running well or not. Basically university Trakindo Main Branch Ternate have had the internal control a good to sales system. it can be seen from the organizational structure, implementation of the internal control, functions related system  credit sales and procedures leasing conducted by the  company, as delay in preparing the items in order by costumers (parts warehouse university trakindo main branch ternate). Basically university Trakindo Main Branch Ternate have had the application of the internal control a good in the system sales.implementation of the internal control system sales conducted is aspects of the organization, the system authorization and procedures recording, practice  healthy and employees with quality in accordance with the responsibilities. On the activities of the  lease university. Trakindo Main Branch Ternate role as the supplier, where the parties provide the  required items by the lessee. Before submitting goods to the lessee, university. Trakindi main Branch Ternatemake agreement after-sales, this is done to maintain and maintain the condition of the goods and made a letter receipt of goods to signed by the lessee, it is also done so as not occur follow-error the future.